Effects of acute exposure to high altitude in acclimatized and non-acclimatized professional soccer players - Cajigal, J.; Araneda, O. F.; Naranjo Orellana, J. (Archivos de medicina del deporte, 2018)
Objective: To evaluate the cardiopulmonary response, gases and acid base balance in a cardiorespiratory maximal test applied to professional football players of first division of Bolivia living at low altitude, during the first six hours after arrival to the high altitude of 3,600 meters. Methods: Eleven Bolivian players living at an altitude of 150 m (lowlanders, LL) and ten highlanders (HL), living at an altitude of 3,600 m, performed the Yo-Yo endurance test with ergospirometry. Base excess (BE), pH, blood gases and capillary blood lactate were determined at 150 m and at 3,600 m seven days later. Results: VO2max (L•min-1) decreased at 3,600 m in both groups, without differences in slopes or interaction between the factors residence and altitude. In LL (p <.001), 3.52±0.46 vs 2.92±0.38. In HL (p <.001), 4.02±0.5 vs 3.41±0.45. The distance covered in the test was lower at 3,600 m in both groups: 1358.2±210.6 vs 1903.64±202.55 m in LL (p <.001) and 1605.0±281.17 vs 2096.0±272.4 m in HL (p <.001). Pre-exercise at 3600 m, LL had a higher pCO2 (38.3 ± 3.0 vs 30.69 ± 1.78 mmHg; p <.001) and a lower satO2 (83.1± 2.7 vs 88.1 ± 1.1%; p <.01). Exercise performed at high altitude produced in LL a higher decrement in pH (-0.258 ± 0.06 vs -0.206 ± 0.03; p <.05) and in BE (-18.73±2.83 vs -12.62±2.13) with no differences in blood lactate (10.8 ± 2.09 vs 9.43 ± 2.1 mmol/L for LL and HL, respectively). Conclusion: During the first six hours at 3,600 m, aerobic performance decrease is similar in LL and HL, although a lower ventilatory response and resting oxygenation of the LL group is found. LL group also showed a greater metabolic acidosis in both altitudes during exercise.